Palladium(II)-catalyzed desymmetrization of 2-alkynylbenzoate-tethered cyclohexadienones for the synthesis of polycyclic compounds - Rai, Archana; Bajpai, Priyam; Gamidi, Rama Krishna; Vanka, Kumar; Das, Utpal (Organic Letters, 2025)
Pd-catalyzed cascade cyclization of 2-alkynylbenzoate-tethered cyclohexadienone was developed for the single step synthesis of isocoumarin-fused dihydrochromenones. This highly atom economical method proceeds via 6-endo-dig cyclization of tert-butyl benzoate with a tethered alkyne. By modulating the reaction solvent and metal catalyst, the methodology was diverted for the purposeful synthesis of either of the E/Z tetra-substituted alkenes.